Foreland Basin Record of Uplift and Exhumation of the Eastern Cordillera, Northwest Argentina - Rahl, Jeffrey (2018)
The style, tempo, and timing of orogenic plateaus such as the Altiplano-Puna in South America are actively debated. Foreland basin strata in northwestern Argentina preserve a record of the eastward propagation, uplift, and erosion of the eastern margin of the high topography of the Puna plateau and Eastern Cordillera. Herein, we present new sedimentologic and geochronologic data from the Neogene foreland basin strata and modern fluvial sediments at 23°S to reveal the timing of growth and erosion of the modern plateau margin. Traditional sedimentologic approaches, including conglomeratic clast counts and sandstone point-counts, combined with detrital zircon U-Pb age distributions preserve robust signatures that track changes in sediment provenance over the past 12 Ma. Growth of the modern plateau edge commenced between 12 and 7 Ma and erected a topographic barrier that cut off the supply of sediment from more westerly sources. Erosion of this rising block has progressively dissected a cover of early Paleozoic sediments of the Mesón and Santa Victoria Groups, leading to deep incision into the pre-Cambrian metasediments of the Puncoviscana Formation that continues today. Detrital apatite and zircon fission track data from the both the Neogene strata and modern streams document erosion of the frontal block at a rate of about 0.6 mm/a.